Correlation between the morning hypertension on ambulatory blood pressure monitoring and the left ventricular mass in children - Hyun Jung Kim; Kyung Hee Kim; Hong Ryang Kil (Korean Pediatric Society, 2014)
PurposeAlthough high morning blood pressure (BP) is known to be associated with the onset of cardiovascular events in adults, data on its effects in children with hypertension are limited. Our retrospective study aimed to define the clinical characteristics of children with morning hypertension (MH) and to determine its associated factors.MethodsWe reviewed 31 consecutive patients with hypertension, confirmed by the ambulatory blood pressure monitoring (ABPM). We divided these patients into 2 groups: the MH group (n=21, 67.7%), morning BP above the 95th percentile for age and height (2 hours on average after waking up) and the normal morning BP group (n=10, 32.3%). We compared the clinical manifestations, laboratory results, and echocardiographic findings including left ventricular hypertrophy (LVH) between the groups.ResultsThe early/atrial (E/A) mitral flow velocity ratio in the MH group was significantly lower than that in the normal morning BP group. In addition, LV mass was higher in the MH group than in the normal morning BP group, although the difference was not statistically significant. The age at the time of hypertension diagnosis was significantly higher in the MH group than in the normal morning BP group (P=0.003). The incidence of hyperuricemia was significantly higher in the MH group than in the normal morning BP group.ConclusionOlder patients and those with hyperuricemia are at higher risk for MH. The rise in BP in the morning is an important factor influencing the development of abnormal relaxation, as assessed by echocardiography. Clinical trials with longer follow-up periods and larger sample sizes are needed to clarify the clinical significance of MH.